MODEL PEMBELAJARAN PENDIDIKAN JASMANI DENGAN PENDEKATAN PERMAINAN - Andri Akhiruyanto (Jurnal Pendidikan Jasmani Indonesia, 2008)
The development of physical education and school sport needs to be maintained. One of the develoment is to focus on the teaching process through methodic in physical education. Physical education programs should be self driven on the students motor deelopment which is able to bring/ uquip them as a qualified final motor, that is by using games approach. This means that it is not only thorugh a movement but also includes social, affective, and cognitif dimension. This motor quality is expected to influence students quality, which in turn will impact on the lifetime human quality. Kata Kunci : Model, Pembelajaran, Pendidikan Jasmani, Permainan